Cumulative evidence for associations between genetic variants in interleukin 17 family gene and risk of human diseases - Liu, Tianyu; Yang, Lei; Lv, Xiaolong; Zuo, Chunjian; Jia, Chenhao; Yang, Zelin; Fan, Chongqi; Chen, Huanwen (Frontiers in Immunology, 2022)
Background: Genetic association studies have elucidated the link of variants in the interleukin 17 (IL-17) family genes with susceptibility to human diseases, yet have obtained controversial outcomes. Therefore, we sought to update comprehensive synopsis of variants in the IL-17 family genes with susceptibility to human diseases. Methods: Our study screened the Pubmed and Web of Science to enroll eligible articles and performed a meta-analysis, then graded the cumulative evidence of significant association using Venice criteria and false-positive report probability test, and finally assessed the function of variants with strong evidence. Results: Seven variants in IL-17 family genes had significant relationships with susceptibility to 18 human diseases identified by meta-analyses. Strong evidence was assigned to 4 variants (IL-17A rs2275913, IL-17A rs8193037, IL-17F rs1889570, IL-17F rs763780) with susceptibility to 6 human diseases (lung and cervical cancer, spondyloarthritis, asthma, multiple sclerosis, rheumatoid arthritis), moderate to 2 variants with risk of 5 diseases, weak to 5 variants with risk of 10 diseases. Bioinformatics analysis suggested that the variants with strong evidence might fall in putative functional regions. Additionally, positive relationships for 5 variants with risk of 4 diseases (based on two datasets) and 14 variants with risk of 21 diseases (based on one dataset) were considered noteworthy. Conclusions: This study offers updated and comprehensive clues that variants in the IL-17 family genes are significantly linked with susceptibility to cervical, lung cancer, asthma, multiple sclerosis, rheumatoid arthritis and spondyloarthritis, and elucidates the crucial role of the IL-17 regions in the genetic predisposition to cancer or noncancerous diseases.